Perioperative myocardial infarction in patients undergoing myocardial revascularization surgery - Pretto,Pericles (2015)
Introduction: Perioperative myocardial infarction adversely affects the prognosis of patients undergoing coronary artery bypass graft and its diagnosis was hampered by numerous difficulties, because the pathophysiology is different from the traditional instability atherosclerotic and the clinical difficulty to be characterized. Objective: To identify the frequency of perioperative myocardial infarction and its outcome in patients undergoing coronary artery bypass graft. Methods: Retrospective cohort study performed in a tertiary hospital specialized in cardiology, from May 01, 2011 to April 30, 2012, which included all records containing coronary artery bypass graft records. To confirm the diagnosis of perioperative myocardial infarction criteria, the Third Universal Definition of Myocardial Infarction was used. Results: We analyzed 116 cases. Perioperative myocardial infarction was diagnosed in 28 patients (24.1%). Number of grafts and use and cardiopulmonary bypass time were associated with this diagnosis and the mean age was significantly higher in this group. The diagnostic criteria elevated troponin I, which was positive in 99.1% of cases regardless of diagnosis of perioperative myocardial infarction. No significant difference was found between length of hospital stay and intensive care unit in patients with and without this complication, however patients with perioperative myocardial infarction progressed with worse left ventricular function and more death cases. Conclusion: The frequency of perioperative myocardial infarction found in this study was considered high and as a consequence the same observed average higher troponin I, more cases of worsening left ventricular function and death.